Immune-enhancing activity of polysaccharides and flavonoids derived from Phellinus igniarius YASH1 - Zhu, Xiaoya; Guo, Ruirui; Su, Xiayu; Shang, Kun; Tan, Conglian; Ma, Junheng; Zhang, Yuemeng; Lin, Dan; Ma, Yueran; Zhou, Min; Yang, Jiale; Wu, Qiqi; et al. (Frontiers in Pharmacology, 2023)
This study aimed to evaluate the immune-enhancing activity and mechanisms of the polysaccharides and flavonoids derived from Phellinus igniarius and to provide a theoretical basis and experimental basis for the development of novel drugs. Wild Phellinus igniarius YASH1 from the Loess Plateau around Yan'an was collected, and polysaccharides and total flavonoids were extracted, isolated and identified from mycelium and sporophore. In vitro antioxidant activity was detected through hydroxyl radical clear ability detection and total antioxidant capacity detection. CCK-8 and trypan blue detection kit were used to detect the effect of extract polysaccharides and flavonoids on the proliferation and phagocytosis ability of immune cells. The protein expression levels of cytokines IL-2, IL-6, IFN-γ, and TNF-α were examined at the cellular and animal levels to assess the effect of the drugs on cytokine secretion by immune cells and immune recovery in immunocompromised mice. The species composition and abundance of gut microbiota and the altered content of short-chain fatty acids in the feces were analyzed to elucidate the possible mechanisms of drugs by 16s RNA amplifiers sequencing and LC-MS-MS. Results showed that both polysaccharides and flavonoids from mycelium or sporophore had antioxidant activity and may stimulate the expression and secretion of IL-2, IL-6, and IFN-γ in immune cells while inhibiting TNF-α expression and secretion and increasing IL-2, IL-6, and IFN-γ expression levels in mice. Polysaccharides and flavonoids from mycelium and sporophore showed different effects on the metabolic response of intestinal SCFAs in mice, and the use of these drugs remarkably changed the species composition and abundance of intestinal flora in mice. Therefore, polysaccharides and flavonoids from Phellinus igniarius YASH1 mycelium and sporophore have in vitro antioxidant activity, and they affect the promotion of cell proliferation, stimulation of IL-2, IL-6, and IFN-γ secretion, and inhibition of TNF-α expression in immune cells. Polysaccharides and flavonoids from Phellinus igniarius YASH1 may enhance immunity in immunocompromised mice and remarkably affect the intestinal flora and content of SCFAs.